العرف وتطبيقاته في الزواج - صويلح، أسماء فخري محمد (مركز البحث العلمي الاسلامي, 2024)
عقد الزواج له أهمية بالغة، لما فيه حفظ لمقصد من مقاصد الشريعة، وهو حفظ النسل فالمشرع الحكيم أولاه عناية بالغة، فشرع للعاقدين حقوقا إن أديت لكليهما صلح حالهما، فكان منه صلاح الأسرة، اللبنة الأساسية لبناء المجتمع ككل فبين البحث أثر العرف في بناء الأحكام الشرعية في بعض الحقوق الزوجية، ومنها أثر العرف في حق الزوجة الغير مدخول بها بالنفقة، وهل للزوج حق الطاعة من زوجته الغير مدخول بها؟ وأثره في تجهيز المرأة نفسها وبيتها واستخدمت الدراسة المنهج الاستقرائي التحليلي، باستقراء الأدلة المتعلقة بالموضوع من الكتاب أو السنة ونصوص الفقهاء، وبتحليل هذه النصوص، ثم الخروج برأي راجح وخلصت الدراسة إلى جملة من النتائج كان أبرزها أن عرف الناس يوجب نفقة الزوجة بعد الدخول ويحجبها عنها قبل الدخول، كما أن العرف لا يعطي حق الطاعة للزوج بالاستئذان والوطء قبل الزفاف، وكان عرف الناس السائد في الأردن بتجهيز الزوج بيت الزوجية وجهاز المرأة. A marriage contract is so important since it preserves one of the purposes of Sharia which is preserving offspring The wise legislator gave it an extreme care; he legislated for the two contracting parties rights as if they are fulfilled, their situation will go right, and from it is family righteousness, the basic pillar to build the society as a whole The study showed the impact of custom in building legal rulings in some marital rights including the impact of custom in the wife’s right who has not been consummated to alimony, and does the husband have the right to be obeyed by his wife who has not been consummated? And its impact in the woman’s preparation of herself and home The study adopted the inductive analytical method by inducting evidence related to the subject from Qur’an, Sunnah or jurists’ texts, and through analyzing these texts and then reaching a good opinion The study concluded to a set of results, the most prominent is that people’s custom imposes the wife’s alimony after consummation of the wife and prevents it before consummation of her The custom also doesn’t the right of obeying to the husband to get permission and consummation before wedding, as it was the people’s in jordan custom to prepare the marital home and the bride’s trousseau
Keywords: الشريعة الإسلامية -- أحكام الزواج -- بيت الزوجية -- الطاعة الزوجية -- نفقة الزوجة